The Role of Ethics, Competence, Auditor Independence, and Audit Fees on Audit Quality: A Literature Review - Krisnia, Irna; Rochayatun, Sulis; Hafandi, Fajar (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Purpose: Auditors are a profession that plays a crucial role in assessing the fairness of financial reports and producing quality reports. This research aims to examine the factors that influence audit quality using a literature review. Method: This research was conducted using the literature review method by collecting theories and previous research results relevant to the theme raised. Results: The results of this research show that empirical research reveals the importance of auditor ethics, auditor competence, auditor independence, and audit fees in maintaining the quality of audit results. The determinants of audit quality are expected to be the auditor's attention so that in the future they can work with more responsibility, objectivity, and honesty in every action and decision. Implications: The implications of this research are expected to be taken into consideration in the formulation of policies related to improving audit quality so that the output of audit results is truly in accordance with the provisions, professional code of ethics of public accountants, and represents the real situation. Novelty: This research is different with the previous research, what will be discussed in this research is the role of ethics, competence, independence, also audit fees in improving the quality of audits. The selected factors have not been combined by previous researchers.